Adoption of Eco-Friendly Waste Reduction Practices in the Clothing Retail Sector in Cape Town - Sweta Patnaik; Asis Patnaik (Textile & Leather Review)
The fashion and textile industry significantly contributes to environmental degradation through unsustainable manufacturing and waste disposal practices, particularly in South Africa's retail sector. This study examines the retail merchandise cycles of two prominent clothing retailers based in Cape Town, South Africa to identify stages that generate substantial fashion and textile waste and proposes a model to enhance sustainability within the industry. Adopting a qualitative, interpretive research paradigm, data were collected through purposive sampling and in-depth interviews with key personnel, primarily buyers, within the selected companies. The research involved mapping and analyzing each retail cycle phase to identify excessive waste generation points. The findings revealed that retailers produce considerable amounts of waste (pre- and post-consumer) due to fast fashion practices and insufficient recycling systems. While both companies acknowledged the importance of sustainability, there was a notable lack of concrete policies and limited visibility into supplier processes concerning environmental impact. The study identified specific departments and operations within the retail cycles responsible for significant waste production, highlighting the need for systemic changes. Based on these insights, an improved retail cycle model was developed emphasizing waste reduction through sustainable sourcing, enhanced recycling initiatives, and stricter supplier compliance measures. The proposed model aims to minimize environmental harm by integrating sustainability into all aspects of the retail process.